Appropriateness of NHS 111 Wales outcomes—using the Call Prioritisation Streaming System: a RAND/UCLA modified Delphi method - Craig Brown; Conrad Fivaz; Rebecca Malin; Mike Brady; Rhiannon Elizabeth Roynon; Peter Noblett (BMJ Open, 2025)
Introduction NHS 111 Wales offers 24-hour telephone assessment, care and referrals for urgent healthcare needs. Call handlers use the newly created and implemented Call Prioritisation Streaming System (CPSS) to assess patients. CPSS is a sophisticated Computer Decision Support Software designed to enhance decision-making processes. It achieves this by integrating individual patient data with a comprehensive computerised knowledge base, employing advanced software algorithms to produce recommendations and dispositions.Objectives While CPSS offers many advantages, its introduction marked a major shift in clinical digital processes. Because of this significant change, it was essential to ensure that the system was functioning correctly and safely after it was implemented. This process of verification and validation is known as postimplementation clinical assurance.Methods An adapted Delphi–Rand/UCLA appropriateness method assessed patient outcomes. In round 1, 189 random anonymised cases were reviewed by international expert clinicians from diverse clinical backgrounds, with consensus measured at >75%. Round 2 involved reviewing non-consensus cases and providing up to 250 characters of context for content analysis.Results In round 1, 49 participants reviewed all 189 cases (total 9913 reviews). In round 2, 41 participants continued to review (total 1746 reviews). Consensus on outcome appropriateness was achieved in 83% (7726 reviews of 144 cases), with a range of 100–76%. Non-consensus occurred in 16.6% (1535 reviews of 45 cases), with a range of 73–18%. For cases with consensus, participants agreed with the outcome 90.5% of the time; for non-consensus cases, outcome agreement was still 60.9%.Discussion Content analysis highlighted the complex interplay of clinician-added value and the aims of prioritisation and streaming. Three themes to enhance CPSS were identified: clinical considerations, referral pathways and system-driven safeguarding identification. No significant clinical safety concerns were found.Conclusion The evaluation of CPSS in NHS 111 Wales shows high levels of outcome appropriateness, assuring patients, service providers and stakeholders. CPSS effectively prioritises and streams patients to appropriate outcomes based on expert clinician consensus.